LabVIEW based Ground Monitoring System for RX200 - Rohmah, Nurul Fahrizatul; Faisa Lailiyul Mutho'Affifah; Fikana Mahardika Cantri; Ardian Wardhana; Mirza Zulfikar Rahmat (BRIN Publishing, 2024)
The implementation and deployment of a comprehensive ground monitoring system for rockets is essential to ensure the safety, efficiency, and success of space missions. Ground monitoring systems for rockets play a crucial role in providing real-time information and analysis of critical parameters during rocket operations, including ground testing and launch operations. The ground monitoring system encompasses various functionalities including the acquisition, processing, visualization, recording and storage of data. The data acquisition process in LabVIEW involves the use of TCP/IP Visa function to collect information. The processing involves various functions such as parsing, flight time calculation, and queue management for efficient data handling and calculations. The data can be recorded and stored using the TDMS function. The system efficiently managed all the received data. This study achieved 90,94% accurate data in processing the entire dataset and obtaining accurate values for calculating flight time. This combination yields precise and dependable data that can be utilized for making real-time decisions, analyzing performance, and evaluating missions after they have been completed.